Is "Trigonum sacrale" a real equilateral triangle? Anatomic consideration of sacral hiatus in adult: A three-dimensional CT study for reliable caudal access. Issue 47 (25th November 2022) - Kuramitsu, Norishige; Nozawa, Satoshi; Sakaguchi, Yasumichi; Yamada, Kazunari; Iwai, Chizuo; Akiyama, Haruhiko
Abstract : This study is the first attempt to examine anatomical characteristics using three-dimensional computed tomography (3DCT) bone images with some parameters, in order to achieve correct and uncomplicated accesses. In addition, the study addresses a long-standing problem in the field and evaluates whether the trigonum sacrale forms an equilateral triangle or not. A detailed anatomic study of the sacral region was carried out on 91 patient 3DCT images. The CT data, in DICOM format, was read into VINCENT software from Fuji Film, with a slice thickness of 0.5 mm. The average length of sacral hiatus was 28.6 ± 8.4 (range 13.8–45.2 mm). The average width of sacral hiatus at the level of sacral cornua was 10.9 ± 2.7 (range 3.8–16.5 mm). The ratio between the length of the oblique and base line formed by the sacral triangle was 0.81 ± 0.12 (range 0.54–1.00). Using 3DCT images translated by the volume rendering technique, we can remove soft tissue from bones virtually. A slice thickness of 0.5 mm makes it a fine image, and permits meticulous measurement, which is different from previous cadaveric studies. Interestingly, our data showed that the ratio between oblique and base line on sacral triangle was <1.0, average 0.81. Findings demonstrated that the trigonum sacrale is not an equilateral triangle. This is useful information for the identification of the sacral hiatus when the landmark-based technique is employed.